Apolipoprotein A1 deficiency in mice primes bone marrow stem cells for T cell lymphopoiesis - Ouweneel, Amber B; Reiche, Myrthe E; Snip, Olga S C; Wever, Robbert; van der Wel, Ezra J; Schaftenaar, Frank H; Kauerova, Soňa; Lutgens, Esther; Van Eck, Miranda; Hoekstra, Menno (Journal of cell science, 2022)
The bone marrow has emerged as a potentially important target in cardiovascular disease as it generates all leukocytes involved in atherogenesis. In the current study, we evaluated whether a change in bone marrow functionality underlies the increased atherosclerosis susceptibility associated with high-density lipoprotein (HDL) deficiency. We found that HDL deficiency in mice due to the genetic lack of hepatocyte-derived apolipoprotein A1 (APOA1) was associated with an increase in the Lin-Sca-1+Kit+ (LSK) bone marrow stem cell population and lymphoid-primed multipotent progenitor numbers, which translated into a higher production and systemic flux of T cell subsets. In accordance with APOA1 deficiency-associated priming of stem cells to increase T lymphocyte production, atherogenic diet-fed low-density lipoprotein receptor knockout mice transplanted with bone marrow from APOA1-knockout mice displayed marked lymphocytosis as compared to wild-type bone marrow recipients. However, atherosclerotic lesion sizes and collagen contents were similar in the two groups of bone marrow recipients. In conclusion, systemic lack of APOA1 primes bone marrow stem cells for T cell lymphopoiesis. Our data provide novel evidence for a regulatory role of HDL in bone marrow functioning in normolipidemic mice.
Keywords: Lymphopoiesis; T-Lymphocytes; lymfopoéza; T-lymfocyty; myši inbrední C57BL; Stem cells; Mice; buňky kostní dřeně; Apolipoprotein A-I; myši knockoutované; LDL-receptory; apolipoprotein A-I; Apolipoprotein; zvířata; Bone Marrow Cells; Bone marrow; Mice, Knockout; Bone Marrow Transplantation; myši; transplantace kostní dřeně; Receptors, LDL; High-density lipoprotein; Mice, Inbred C57BL; Animals